TYPES AND FUNCTIONS OF ADDRESS TERMS USED BY IPMK-SB “KAMPAR STUDENTS STUDYING IN PADANG” - Rahmadani Rahmadani; Delvi Wahyuni (Universitas Negeri Padang, 2018)
Address terms is the study of addressing people in speech or writing by using a word, phrase, name, title or some combination of these. This research paper is aimed to investigate types and functions of address terms used by people in IPMK-SB “Kampar Students Studying in Padang”. This research paper uses Wardhaugh (2006) and Esmae’li (2011) theories about types and functions of address terms. This study used descriptive qualitative approach supported by quantitative. The result of this research showed that from seven theories of types of address term based on Wardhaugh, there were found only four types of address term used by IPMK-SB. They were special nickname, kinship terms, pet name and title only. The biggest percentage goes to kinship terms (55,38%) folowed by special nickname (37,95%), and pet name (4,62%). The smallest percentage goes to title only (2,05%). The reason why number of types address terms found smaller because the limitation of this research only did in secretariat of IPMK-SB. Then, for the functions, the writer found five functions of address terms based on Esmae’li and Wardhaugh theories. They were attract people attention, show intimacy, show politeness, show power differential, and reflect identity. The first dominant function of address term was show intimacy (47,69%), followed by attract people attention (37,44%), show politeness (9,23%), and reflect identity (3,59%). The last dominant function of address term was show power differential (2,05%).